Passive rate‐based separation in collisional flows. Issue 9 (20th April 2017) - Bartlow, Diana Lievano; Bhattacharya, Tathagata; McCarthy, J. J.
Abstract : The passive separation of a binary mixture of spherical particles is accomplished using a laboratory scale quasi‐two‐dimensional inclined board such that gravity alone drives the flow of the mixture through a static array of obstacles. Experimental results compare well with simulations both qualitatively and quantitatively. An increase in separation is observed for increasing board length, whereas a decrease in separation is observed as the solid fraction (area coverage) of particles increases. The possibility of designing green technology for solid‐solid separations by taking advantage of particle properties that aid naturally occurring segregation is demonstrated. A probability‐based model is suggested as a way to predict the viability of separation between particle types as a function of particle size and coefficient of restitution. It should be noted that size separation is achieved despite peg spacings that are larger than both particles in a mixture. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3717–3727, 2017